Entre dois agostos: o Conselho de Educação do Ceará na década de 1970 – 1979 - Lima, Jeimes Mazza Correia (2013)
The study on the performance of the Board of Education of Ceará aims at understanding how the institution structured through educational legislation in force in the 1970s, school education Ceará. This organization was led by opinions and resolutions specific, so the means available for this purpose, providing the understanding of the possible existence of legal interpretations by the referees, the Board of Education, giving them an ability to act in Ceará extrapolating and distorting their specific functions, which was to interpret and apply the law determined by educational reform, 1971, by Law 5692/71, in response to a determination of the period of authoritarian rule, endowed with characteristics related restrictions on individual freedom and collective, common at the time. For it was used to analyze a set of documents, written sources, produced over a decade by the institution with their official, stating interpretations, positions and definitions of school education and political momentum. From this documentation, with mediation from other sources relevant to the season, it was noticed that after its re-foundation in 1965 by the governor of Ceará Virgilio Tavora the Council sought to legitimize their actions in the local society, and gradually, coercively established an organization of education school in Ceará in compliance with standards, rules and legislation. Although an institution linked to the State no clear indication that developed a set of administrative acts restrictive of freedom, besides adopting punishments schools or their members, directors, secretaries and school teachers as well as students, attending deliberation direct bodies of political repression developed in the period. With this it is possible to infer that: was ineffective use of the Board of Education of Ceará in 1970 with the purpose to serve the political repression of opposition movements to the authoritarian regime largely attended by high school students.